Вдосконалення менеджменту забезпеченням фінансово-економічною безпеки підприємства - Виходець, Юлія Миколаївна; Vykhodets, Yuliia (ЦНТУ, 2024)
Метою даної роботи є дослідження системи менеджменту забезпечення фінансово-економічної безпеки на підприємстві та обґрунтування напрямів її удосконалення. Предметом дослідження є стан фінансово-економічної безпеки підприємства. Об’єктом дослідження роботи є система забезпечення фінансово-економічної безпеки на підприємстві ПрАТ «Гідросила АПМ». В роботі були поставлені такі завдання: визначити теоретичні засади формування фінансово-економічної безпеки підприємства; дослідити стабільність фінансового стану господарюючого суб’єкта у довгостроковій перспективі в умовах змін зовнішнього та внутрішнього середовищ; визначити напрями підвищення ефективності управління фінансово-економічною безпекою підприємства. The purpose of this work is to study the management system of financial and economic security at the enterprise and to substantiate the directions of its improvement. The subject of the study is the state of financial and economic security of the enterprise. The object of the study is the system of ensuring financial and economic security at the enterprise PJSC "Hydrosila APM". The work sets the following tasks: to determine the theoretical foundations of the formation of financial and economic security of an enterprise; to study the stability of the financial condition of an economic entity in the long term in the face of changes in the external and internal environments; to determine the directions for improving the efficiency of managing the financial and economic security of an enterprise.
Improvement of management by ensuring the financial and economic security of the enterprise
Keywords: фінансові показники; інформаційні технології; фінансовий менеджмент; контролінг; financial indicators; information technology; financial management; controlling